Opening spaces for Critical Pedagogy through Drama in Education in the Chilean classroom - VILLANUEVA VARGAS, MARÍA CATALINA (Trinity College Dublin. School of Education. Discipline of Education, 2019)
The links between Applied Theatre and Critical Pedagogy (CP), a social justice oriented educational paradigm, have been studied by a number of authors (Dawson, Cawthon, & Baker, 2011; Doyle, 1993; Freebody & Finneran, 2013; Grady, 2003; O'Connor, 2013). However, they have seldom been analysed in a Latin American school context, like Chile, a country characterised by a neoliberal educational system (Cavieres-Fernández & Apple, 2016). This study explores how Drama in Education (DiE) opened up spaces for CP in Chilean teachers' practices, analysing the factors that facilitated or hindered the opening of such spaces. DiE is understood here as a branch of Applied Theatre that uses theatrical and dramatic strategies as a methodology for teaching-and-learning across the curriculum (Ackroyd, 2007). A case study approach was adopted for this exploration, focusing on a Continuing Professional Development (CPD) Programme designed and facilitated by the researcher in a School in Santiago, Chile, in 2016. This included a 15-hour Workshop where fifteen teachers learned diverse DiE strategies, reflecting on their potential for CP. Afterwards, eight teachers collaborated with the researcher coplanning and coteaching lessons where DiE was applied. Participant and non-participant observation, interviews, questionnaires, and document analysis methods were used to gather data, which was analysed thematically with the assistance of the computer software NVivo 10. DiE opened up several spaces for CP in these teachers' practices. It enhanced the dialogic quality of their lessons by encouraging them to collaborate with their students. DiE helped teachers to exert their authority in non-authoritarian ways. It allowed them to enhance participation opportunities for students, by involving them physically, emotionally, and cognitively. However, when DiE activities caused embarrassment or hinged on factual knowledge, habitual classroom inequalities were reproduced. DiE also helped some teachers to promote conscientization, that is, critical reflection and action about social oppression and transformation (Freire, 2000). Findings suggest that there is potential in performative DiE strategies, like still-images, to behave as Freirean codifications (Pompeo Nogueira, 2002), eliciting conscientization in students. This potential was also found in role-playing. However, such potential was restricted in these teachers' practices due to a disconnection between the DiE lessons and their students' thematic universe, which decreased the relevancy of the experiences for their own lives. This study corroborated the importance of emotional engagement for critical reflection in Applied Theatre (Bundy, Dunn, & Stinson, 2016), and that engagement is facilitated when teachers offer a journey of exploration to students through a coherent sequence of DiE activities (Dunn & Stinson, 2011). This study found that DiE helped teachers to promote critical thinking, metacognition, and motivation, key precursors of conscientization in this specific context. This study found that teachers' opening of spaces for CP through DiE required a degree of artistry. Teachers' orientations were also a factor as they seemed to determine the aspects of CP embraced by teachers through their practice of DiE. Finally, the role of the researcher as leader of the Programme both enabled and hindered teachers' opening of spaces for CP through DiE. This suggests that CPD Programme leaders require significant expertise to guide teachers fruitfully. These findings expand available knowledge on Applied Theatre and CP, while also contributing to strengthen the emergent field of Applied Theatre in Chile.
APPROVED
Keywords: Drama in Education; Paulo Freire; Critical Pedagogy; Applied Theatre; Continuing Professional Development; Chile